2022
DOI: 10.3126/jki.v8i1.52934
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Customer Satisfaction on Loyalty: A Moderating Role of Corporate Communication in the Banking Sector

Abstract: In the 21st global competitive arena, the ultimate objective of any institution is to transform satisfied customers into loyal customers. Customer loyalty is highly affected by the satisfaction they obtain out of any service. Therefore, it is crucial to understand the relationship between customer satisfaction and customer loyalty. This study aims to examine the effect of customer satisfaction on customer loyalty with the mediating role of corporate communication. To collect data for the study, a convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…For instance, Mistrean (2023) suggests that understanding the nature of loyalty and the factors that contribute to it, such as switching costs, can help banks retain customers. Moreover, a study by Mishra (2022) found that customer satisfaction, closely related to perceived switching costs, positively influences customer loyalty. Therefore, switching costs act as a barrier and significantly affect customer loyalty in the banking sector (Mishra, 2022;Mistrean, 2023).…”
Section: Switching Costsmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Mistrean (2023) suggests that understanding the nature of loyalty and the factors that contribute to it, such as switching costs, can help banks retain customers. Moreover, a study by Mishra (2022) found that customer satisfaction, closely related to perceived switching costs, positively influences customer loyalty. Therefore, switching costs act as a barrier and significantly affect customer loyalty in the banking sector (Mishra, 2022;Mistrean, 2023).…”
Section: Switching Costsmentioning
confidence: 99%
“…Moreover, a study by Mishra (2022) found that customer satisfaction, closely related to perceived switching costs, positively influences customer loyalty. Therefore, switching costs act as a barrier and significantly affect customer loyalty in the banking sector (Mishra, 2022;Mistrean, 2023).…”
Section: Switching Costsmentioning
confidence: 99%
See 3 more Smart Citations